Effect of Gamma Irradiation on Some Carcinogenic Polycyclic Aromatic Hydrocarbons (PAHs) in Wheat Grains. (19th October 2016) - Khalil, Ayman; Albachir, Mahfouz; Odeh, Adnan
Abstract : Gamma irradiation effects on seven carcinogenic polycyclic aromatic hydrocarbons (PAHs) were investigated. 0, 1, 5, 10, and 15 kGy of gamma irradiation doses were used in wheat grain treatments. PAHs were extracted and their concentrations at each doses were determined using HPLC equipped with fluorescence analysis. Results demonstrate a reverse relationship between PAHs concentrations and gamma irradiation doses. PAHs concentrations decreased when the gamma irradiation dose increased. The total of PAHs concentration decreased by 35% at 1 kGy while the reduction exceeded 70% for doses higher than 5 kGy. PAHs reduction in irradiated grain samples versus irradiation dose was linear/exponential depending on the structure of PAHs compounds. Results could be of great importance when gamma irradiation is used for the elimination of PAHs from wheat grains.